Women's work in Britain and France : practice, theory and policy / Abigail Gregory and Jan Windebank. - Gregory, Abigail (Macmillan, 1999)
This text replaces the conventional focus upon encouraging women's increased insertion into employment as the principal strategy for achieving progress in gender relations, with a new focus on changing men's work patterns.